School Leadership in The Digital Transformation of Islamic Educational Institutions - M. Arif Musthofa (LPPM Universitas Bina Bangsa, 2026)
Digital transformation in education demands significant changes in school structures and cultures, with principals as key leaders integrating technology in learning, management, and communication. Transformational and digital leadership is the key to creating an educational environment that is responsive to technological developments and the needs of the times. The research aims to analyze the role of transformational leadership in driving digital innovation through vision and collaboration, identify strategies to overcome implementation resistance, evaluate its impact on educational performance and sustainability, and compare the effectiveness of transformational and transactional styles to